Menelisik Hukum Jual Beli Kredit Melalui Kajian Tafsir Al-Quran - Khozainul Ulum (Universitas Islam Lamongan, 2017)
In fulfilling the needs, human beings tend to do various ways and always looking for ease. In the context of the fulfillment of economic needs, for example, not everyone can get easy access to be able to get the needs. The purchasing power of each person always refers to the stability of the amount of income earned every day or every month. Therefore, it is not surprising that payment system in transaction of buying and selling that try to make easy for consumer to get what is wanted, that is credit payment. In Islam, payments in credit transactions are known as nasīah. This paper will trace the arguments of the Quran that are related to the payment of sale and purchase on credit. From the Quranic interpretation of sura al-Baqarah verse 282 and 283 above with respect to the transaction on credit, it can be summarized as follows. First, the transaction on credit in Islam is not forbidden and not makruh. In other words, it is allowed even though the price of goods sold in credit is more expensive than the price in cash. Second, in a transaction on credit, it is ordered to make record and witness to the requierments and conditions of the transaction. The purpose of these records and testimony is to safeguard the rights of each transactor and to avoid disputes in the future. In this case, ulama have difference on the form of such recording and testimonies. One side believes that the order is obligatory (wajib), and the other side thinks it sunnah. According to me, after seeing the purpose of record and testimony of the above transactions, the record and testimony in the transaction is wajib.Third, transaction made in cash (yadan bi yadin), according to the author, is also required to record and testimony. This is a form of caution, because at the moment there are many disputes in transactions that arise in the community, even though they have done the recording and testimony. Fourth, note of treaty and the receipts included in each transaction at the present have an important meaning to safeguard the rights and obligations of each party conducting the transaction. Moreover, note of treaty and receipt are a valid and concrete evidence explaining the truth of the transaction. Keywords: Credit Sale, Quranic Interpertation Approach